2018
DOI: 10.1111/iwj.12904
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin accelerates cutaneous wound healing via multiple biological actions: The involvement of TNF‐α, MMP‐9, α‐SMA, and collagen

Abstract: Curcumin, a constituent of the turmeric plant, has antitumor, anti-inflammatory, and antioxidative effects, but its effects on wound healing are unclear. We created back wounds in 72 mice and treated them with or without topical curcumin (0.2 mg/mL) in Pluronic F127 gel (20%) daily for 3, 5, 7, 9, and 12 days. Healing in wounds was evaluated from gross appearance, microscopically by haematoxylin and eosin staining, by immunohistochemistry for tumour necrosis factor alpha and alpha smooth muscle actin, and by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 46 publications
4
72
0
Order By: Relevance
“…For example, Chen [27] found that inhibiting the expression of IL-6 and IL-10 could reduce the in ammatory response to promote wound healing. The secretion of VEGF in the healing process also exerts and important effect, and VEGF will promote the proliferation of vascular endothelial cells and their survival, accelerating the formation of new blood vessels [28][29][30][31]. The blood vessels are the channels of nutrient delivery in the body [32], and ensure that the tissues and organs are provided with su cient requirements for new skin formation [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen [27] found that inhibiting the expression of IL-6 and IL-10 could reduce the in ammatory response to promote wound healing. The secretion of VEGF in the healing process also exerts and important effect, and VEGF will promote the proliferation of vascular endothelial cells and their survival, accelerating the formation of new blood vessels [28][29][30][31]. The blood vessels are the channels of nutrient delivery in the body [32], and ensure that the tissues and organs are provided with su cient requirements for new skin formation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin (1,7-bis-(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione), a polyphenol extracted from the plant curcuma longa with anti-inflammatory and free-radical scavenging function, has been proven to be an effective agent against wound [3][4][5], but the exact mechanisms remain unclear. However, the clinical application of curcumin is limited due to its poor water solubility and low bioavailability [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on the polyphenol curcumin which has been widely used for centuries in the traditional medicines of China and India. Curcumin exhibits some antimicrobial, antioxidant, antiseptic, and anti‐inflammatory properties, besides expressing a potential matrix metallo protease (MMP)‐inhibiting activity, and has recently aroused much interest for wound‐healing applications . It has also been demonstrated to accelerate wound healing via different biological processes, such as regulation of cytokine levels and MMP9 concentration in wound beds.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated to accelerate wound healing via different biological processes, such as regulation of cytokine levels and MMP9 concentration in wound beds. Together, these factors enhance tissue granulation through fibroblast proliferation, help to deposit new collagen, stimulate neoangiogenesis, and regenerate epithelial layers …”
Section: Introductionmentioning
confidence: 99%